Kognitivne in duševne motnje pri osebah po COVID-19 - Čižman Štaba, Urša (Rehabilitacija (Ljubljana), 2021)
There is an increased attention to cognitive and psychological complications associated with coronavirus disease. Recently, the term "brain fog" has become more common in the literature, referring to a set of psychological symptoms, behavioral changes, and cognitive impairments experienced by patients with central nervous system infection as a consequence of SARS-CoV-2 infection. Given the occurring symptoms, it is becoming increasingly clear that clinical psychologists have an important role in assessing, guiding, and treating COVID-19 survivors within interdisciplinary care. However, the clinical approach may deviate from the usual procedures used by clinical psychologists. The paper shares an insight of the literature on cognitive consequences and mental disorders that occur after COVID-19 and guidelines for clinical psychological treatment.
Keywords: clinical psychology; cognitive disorders; COVID-19; duševne motnje; klinična psihologija; kognitivne motnje; mental disorders; neuropsychology; nevropsihologija; rehabilitacija; rehabilitation; Rehabilitation Research